Hubungan Umur Awal Menopause dan Status Penggunaan Kontrasepsi Hormonal dengan Kejadian Kanker Payudara - Nani, Desiyani (Jurnal Keperawatan Soedirman, 2009)
Breast cancer represent abnormal growth of body tissue cells that become malign. The cancer is second highest of death cause and represent 26% of all of cancer type in women and responsible for 18% of death. Breast cancer caused by several factor such us menarche age, first birthing age, the amount of children, menopausal age, fibrocystic disease chemistry, hormonal contraception status, ionic radiation exposures, and family cancer chemistry. This research was conducted to study several factors (menopausal age, hormonal contraception status) that have relationship with breast cancer insidence at menopausal women in Pertamina Hospital in Cilacap, Central Java. Retrospective analytical survey by case control approach. Sampling method was purposive sampling. Sample definite around 60 people which divide 30 people at case group and 30 people in control group which exclution and inclution criteria. Chi square was applied to analyze the data. There is no significant relations between menopausal age (p = 0,425 ), and hormonal contraceptive status (p = 0,144) with breast cancer incidence at menopausal women in Pertamina hospital, Cilacap, Central Java.There is no significant relations between menopausal age (p = 0,425 ), and hormonal contraceptive status (p = 0,144) with breast cancer incidence at menopausal women in Pertamina hospital, Cilacap, Central Java.